Pengelolaan Piutang untuk Profitabilitas Bisnis Jasa Hotel - Muhammad Rofiudin; Nurtjahja Juniarsa; Defia Nurbatin; Reza Adytia Dwiputra (Jur. Akuntansi, Politeknik Negeri Malang, 2019)
This study aims to explore the management of accounts receivable which has an impact on the profitability of hotel room rental services at Royal Orchid Garden Batu. This study uses an explanatory research approach by reviewing the data of accounts receivable from PT Royal Orchid Garden Hotel in 2013 to 2017. Supervision of the level of accounts receivable turnover through a strict credit policy has an impact on increasing business profitability of the Hotel. The novelty of this research lies in the review of accounts receivable turnover in the hospitality service business.